STUDI LITERATUR : EFEKTIVITAS MODEL PEMBELAJARAN PENGAJUAN DAN PEMECAHAN MASALAH DALAM MENINGKATKAN KEMAMPUAN BERPIKIR KREATIF SISWA - Lidia Aprilia Tangdilintin; Rifka Adriani Aswar; Asdar (LPPM Institut Ahmad Dahlan Probolinggo, 2026)
Mathematical creative thinking skills are an important competency in 21st century mathematics learning, but they are still relatively low due to the dominance of routine procedure-oriented learning. This study aims to examine the effectiveness of the Problem-Based Learning Model (JUCAMA) in improving students' mathematical creative thinking skills. The method used is a literature study with a qualitative descriptive approach to relevant national journal articles published in the last eleven years. The analysis was conducted through a process of identification, selection, evaluation, and synthesis of research findings to obtain a comprehensive picture. The results of the study show that the consistent application of the JUCAMA model has a positive impact on improving mathematical creative thinking skills at various levels of education, as demonstrated by the development of indicators of fluency, flexibility, originality, and elaboration in solving and posing mathematical problems. In addition, the effectiveness of the model is optimized when supported by appropriate learning tools and media. Thus, JUCAMA can be used as an alternative innovative learning model oriented towards developing student creativity in mathematics learning.